2018
DOI: 10.2147/opth.s153509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal biomechanics after myopic small-incision lenticule extraction compared to LASIK: an ex vivo study

Abstract: PurposeTo investigate ex vivo potentially different corneal biomechanical properties after small-incision lenticule extraction (SMILE) versus LASIK for myopic correction.MethodsThirty human donor corneas were subjected to either myopic SMILE or femtosecond laser-assisted LASIK. Donor corneas were assigned to six investigative groups: Group A, −3.00 D (diopters) SMILE; Group B, −8.00 D SMILE; Group C, −3.00 D LASIK; and Group D, −8.00 D LASIK. Additionally, two control groups were formed: Group E, SMILE and Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…Biaxial stress–strain measurements were superior to corneal strip tensiometry. Previous studies have also shown that sclera exhibited a stress-hardening response when subjected to gradual tensile loads, demonstrating nonlinear characteristics. , The present study also indicated that the sclera is elastic and exhibits an obvious hysteresis phenomenon. This further indicates that the whole sclera exhibits major mechanical anisotropy.…”
Section: Discussionsupporting
confidence: 85%
“…Biaxial stress–strain measurements were superior to corneal strip tensiometry. Previous studies have also shown that sclera exhibited a stress-hardening response when subjected to gradual tensile loads, demonstrating nonlinear characteristics. , The present study also indicated that the sclera is elastic and exhibits an obvious hysteresis phenomenon. This further indicates that the whole sclera exhibits major mechanical anisotropy.…”
Section: Discussionsupporting
confidence: 85%
“…The similarity of the biomechanical effects after SMILE and FS-LASIK might sustain this parallel occurrence of myopic regression. Kanellopoulos [ 18 ] showed that the SMILE procedure reduces the tensile strength in lower myopic corrections while retaining a similar tensile strength in higher myopic correction compared with LASIK. Magallanes et al [ 19 ] proved that the significant loss of corneal strength following large myopic corrections might lead to refractive regression.…”
Section: Discussionmentioning
confidence: 99%
“…Although this scoring system was developed for LASIK, it was also applied here given that a modified version does not yet exist for SMILE. Moreover, we believed that the risk factors for ectasia should be applied uniformly to both procedures although the biomechanical superiority of SMILE over LASIK is attributed to the stromal tissue removal at the deeper layers [ 30 ]. Hence, the results of the Randleman scoring system may be used as a supplementary reference for the ectasia risk after SMILE, and moderate-to-high risk patients should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%